Biosynthesis of histone messenger RNA employs a specific 3' end endonuclease - Pettinati, I; Grzechnik, P; Ribeiro De Almeida, C; Brem, J; McDonough, M; Dhir, S; Proudfoot, N; Schofield, C (eLife Sciences Publications, 2018)
Replication-dependent (RD) core histone mRNA produced during S-phase is the only known metazoan protein-coding mRNA presenting a 3' stem-loop instead of the otherwise universal polyA tail. A metallo β-lactamase (MBL) fold enzyme, cleavage and polyadenylation specificity factor 73 (CPSF73), is proposed to be the sole endonuclease responsible for 3' end processing of both mRNA classes. We report cellular, genetic, biochemical, substrate selectivity, and crystallographic studies providing evidence that an additional endoribonuclease, MBL domain containing protein 1 (MBLAC1), is selective for 3' processing of RD histone pre-mRNA during the S-phase of the cell cycle. Depletion of MBLAC1 in cells significantly affects cell cycle progression thus identifying MBLAC1 as a new type of S-phase-specific cancer target.